Forecasting models for the biogas emissions from landfills. Issue 18 (16th September 2016) - Kwiatkowski, Tomasz; Żygadło, Maria
ABSTRACT: The forecasting of the biogas emissions using the Environmental Protection Agency and Research And Development Centre For Cities Ecology models was performed for the municipal landfill. The results of the predictions are compared with the monitoring results carried out at the landfill facility in the field studies.